En Balance: The Contribution of Physical Activity to the Efficacy of Spanish Diabetes Education of Hispanic Americans with Type 2 Diabetes - Dequina A. Nicholas; Lorena M. Salto; Kristen Lavelle; Joy Wilson; W. Lawrence Beeson; Anthony Firek; William H. R. Langridge; Zaida Cordero-MacIntyre; Marino De Leon (Journal of Diabetes Research)
Purpose. En Balance, a culturally sensitive diabetes education program, improves glycemic control in Hispanics with type 2 diabetes. The program emphasized diet, physical activity, and other factors important for glycemic control. However, the individual contributions of these education factors are unclear. The purpose of this study is to assess the contribution of physical activity to the success of En Balance in improving the health of Mexican Americans with type 2 diabetes. Methods. A retrospective study was conducted with plasma samples collected pre- and post-3-month study. Samples from 58 (18 males and 40 females) Hispanic subjects with type 2 diabetes were analyzed for the concentration of kynurenines, known to decrease in response to exercise. After three months, health outcomes for the active group (decreased kynurenines) and the rest of the cohort were evaluated by paired Wilcoxon signed-rank test. Results. Half of the subjects had increased kynurenine levels at the end of the educational program. We found that the subjects in the active group with decreased kynurenine concentrations displayed statistically greater improvements in fasting blood glucose, A1C, cholesterol, and triglycerides despite weight loss being higher in the group with increased kynurenine concentrations. Conclusions. En Balance participants with decreased kynurenine levels had significantly improved glycemic control. These data suggest that physical activity significantly contributes to the success of the En Balance education program. This analysis indicates that diabetes public health educators should emphasize the benefit of physical activity on glycemic control even in the absence of major weight loss.